Analisis Profesionalisme Kerja Pegawai Pada Kantor Camat Kapur IX Kabupaten Lima Puluh Kota - Rangga Saputra; Nurmasari Nurmasari (UIR Press, 2020)
This study aims to find out and analyze the Professionalism of Employee Work at the Office of Kapur IX Sub-District, Fifty City District. The work professionalism assessment indicators used include competence, effectiveness, efficiency, and responsibility. This type of research is descriptive quantitative survey, which prioritizes questionnaires as a tool for collecting data and data collected with this tool and then becomes the main raw material for analyzing empirical conditions and objectivity of the existence of objectives at the study site. The population and samples in this study were 40 people. The types and data collection techniques used consisted of, primary data collected using questionnaire list techniques and interviews and secondary data collected using observation techniques. While the data analysis technique used is to use a frequency table tool. Based on this analysis technique the researcher assessed and concluded that the Analysis of Employee Work Professionalism at the Office of the Capur IX District of Fifty City District was categorized quite well. The inhibiting factor is the absence of CCTV installed in the Kapur IX sub-district office, so supervision of the professionalism of employees is not optimal. Then some employees often delay during recess. In addition, the services provided by employees in the Kapur IX sub-district office are always slow and not on time.